Surgical emergencies, onco-surgeries and colorectal surgeries in COVID-19 pandemic: practical advice based on the global experience and at Dr. D. Y. Patil Medical College, Hospital and Research Centre - Gowtham, Thakut; Kadiyal, Abhinandan Milind; Murchite, Sheetal A.; Kulkarni, Rajendra Madhukar; Gaikwad, Vaishali Vinayak (International Surgery Journal, 2020)
The existing coronavirus 2019 (COVID-19) pandemic is challenging healthcare systems at global level. We provide a practical strategy to reform pathways of emergency elective onco-surgery and colorectal surgery in the COVID- 19 pandemic. The novelists, from areas affected by the COVID-19, thought to outline the key-points to be conferred. Responsibilities were allotted, concerning specific characteristics of surgical emergencies, onco-surgery and colorectal surgery during the pandemic, including the administrative management of the catastrophe in India. The endorsements were collected and summarized. During the swift spread of COVID-19, it remains thoughtful to halt non-cancer procedures and prioritize surgical emergencies. Endoscopy, proctological procedures have to be completed selectively. With colorectal emergencies, a conservative approach is recommended. Detailed procedures should be followed when operating on COVID-19 patients, using committed personal protective equipment and adhering to specific rules, containing minimally invasive surgery. These guidelines summarize the strict instruction of entry/ exit into theatres and operating block as well as advice on performing procedures carefully to decrease risk of contracting the virus. It is likely that restructuring of health system is required, at central, state, and district levels. A description of the strategy adopted in Dr. D.Y. Patil Medical College Hospital, Kolhapur is provided. Evidence on the management of patients requiring surgery for surgical emergencies, onco-surgery and colorectal conditions during the COVID-19 pandemic is presently deficient. Healthcare professionals have succeeded with high volumes of surgical patients during the pandemic, could be useful to alleviate some risks and decrease exposure to other patients, public and healthcare staff.